How Does Stroke Affect Skeletal Muscle? State of the Art and Rehabilitation Perspective - Azzollini, Valentina; Dalise, Stefania; Chisari, Carmelo (Frontiers in Neurology, 2021)
Long-term disability caused by stroke is largely due to an impairment of motor function. The functional consequences after stroke are caused by central nervous system adaptations and modifications, but also by the peripheral skeletal muscle changes. In fact, the nervous and muscular systems work together and are strictly dependent in their structure and function, through afferent and efferent communication pathways with a reciprocal "modulation". Knowing how altered interaction between these two important systems can modify the intrinsic properties of muscle tissue is essential to find the best rehabilitative therapeutic approach. Traditionally the rehabilitation effort has been oriented towards the treatment of the central nervous system (CNS) damage with a central approach, overlooking the muscle tissue. However, to ensure greater effectiveness of treatments, it should not be forgotten that muscle can also be a target in the rehabilitation process. The purpose of this review is to summarize the current knowledge about the skeletal muscle changes, directly or indirectly induced by stroke, focusing on to the changes induced by the treatments most applied in stroke rehabilitation. The results of this review highlight changes in several muscular features, suggesting specific treatments based on biological knowledge; on the other hand, in standard rehabilitative practice a realist muscle function evaluation is rarely carried out. We provide some recommendations to improve a comprehensive muscle investigation, a specific rehabilitation approach, and to draw research protocol to solve the remaining conflicting data. Even if a complete multilevel muscular evaluation requires a great effort by a multidisciplinary team to optimize motor recovery after stroke.